Monitoring Hygienic Measures for Decreasing Salmonella Occurrence in Scalding Tank Water of a Turkey Slaughterhouse - Francisco Arispón; Nazaret Cano; Rafael Jordano; Luis M. Medina (Applied Sciences, 2023)
The objective of this work was to test different treatments based on the temperature and acidification of scalding tank water throughout the day in a turkey slaughterhouse under industrial conditions in order to decrease the occurrence of Salmonella. After controlling the scalding tank water under usual conditions, the following measures were taken: (a) the temperature was increased to 60 °C and 70 °C for 15 min at the halfway point of the day; (b) the scalding water was acidified and six different initial pH levels were tested. Both measures which were tested (heating and acidification of scalding water) showed efficiency in reducing the occurrence of Salmonella during the scalding step. In order to prevent the disadvantages associated with the hardest measures in each case, we propose that scalding water be heated to 70 °C for 15 min without carcasses, which can be repeated if the disadvantages of the exposed costs and resources of processing are acceptable. Regarding acidification, a suitable measure would be an initial pH of 4.0 or any treatment that keeps the pH of the scalding water below 4.5, using acid that does not affect the final quality of the products and/or the elements involved.